Responsibilities of the Ordinary in proceedings concerning offences reserved to the Dicastery of the Doctrine of the Faith - Cisek, Krzysztof (Prawo Kanoniczne, 2023)
The law imposes a number of duties on the Ordinary in proceedings concerning offences reserved to the Dicastery for the Doctrine of the Faith. The powers and actions to be taken by the Ordinary may be of a different nature, depending on whether the notitia criminis that has reached him concerns a delict against the faith (heresy, apostasy, schism) or any of the more grave delicts committed against morals and the celebration of the sacraments (delicta graviora). According to the norms of the law (Norms regarding delicts reserved to the Congregation for the Doctrine of the Faith), the Ordinary has greater autonomy of action with regard to delicts against the faith, since it is up to him to conduct a judicial trial in the first instance or an administrative trial, as well as to absolve in the external forum the excommunication incurred latae sententiae. On the other hand, in the case of the more grave delicts in the celebration of the sacraments and contra mores (delicta graviora), the Ordinary, having received knowledge of the offence, which is at least probable, should carry out a preliminary investigation and then send a copy of the case file to the Dicastery for the Doctrine of the Faith. Further decisions in the case are taken by the Dicastery, which may then entrust the Ordinary to carry out the indicated actions.